Prototipo electrónico de monitoreo remoto de la calidad del agua para análisis de temperatura, oxígeno disuelto y pH en criaderos de tilapia en la granja piscícola Los Cristales- Hobo (Huila). (2024)
The importance of monitoring variables such as dissolved oxygen, pH and temperature, is crucial for the planning of activities such as water replacement, amount of food to be supplied and the operation of the aerator equipment, which if not controlled lead to problems such as mortality, slow growth of animals among others, seriously affecting the efficiency in the production of mojarra in ponds on land in the fish farm Los Cristales; The objective of the project is to develop an electronic prototype for remote monitoring of water quality for analysis of the variables mentioned; the methodology used is based on the development of a device based on an Arduino Uno with WiFi onnectivity through the ESP8266 module. This device connects to an Internet network and captures data from sensors of the parameters to be measured. The data is digitized and sent to a MySQL storage server, and simultaneously displayed graphically and in real time on an HTML web page. The results showed that the degree difference between the HANA sensor and DS18B20 varies from 0.2 to 0.6 degrees Celsius, which shows that there is a slight difference between the temperature readings. It is concluded that by allowing real time monitoring of water quality in a fingerling planting lake, crop decision making can be improved and made more efficient, minimizing future product losses.